PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH/ANGGOTA KOPERASI JASA KEUANGAN SYARIAH (KJKS) BMT INSAN KAMIL SOLO - Rineta, Dian; Bisri (UNIBA Surakarta), slamet Riyadi; maryam, siti (Manajemen Bisnis Syariah, 2012)
The paradigm of Islamic economy is based on the God factor has become thetrend of economic system in many countries, including Indonesia in the past severalyears. The Islamic economic system in Indonesia began developed in 1992. Thedevelopment of Islamic economy itself is able to control the Islamic valueimplementation of the society economic life. In business practices, the consciousnessof etiquette, honesty and other Islamic principles appear.Some approaches done to attract the sympathy of society, whether throughfacilities increasie , technology application or human resources. The competition togive the best to the customers, have placed the customers as the decision makers. Themore similar companies operated, offers various products and services, this makessociety determine correct choice for their needs.In the tight competition situation, customers often have loyalty to BMT becausemany alternatives are given to the customers and they will choose the most profitableoffer for them. The aims of this research is to analyze the influence of servicesatisfaction towards customers/members loyalty to KJKS BMT Insan Kamil Solo.This research problem is purposed to identify how the influence of service ondimension of reliability, assurance, tangibles,empathy responsiveness, price, accessand customer intimacy towards satisfaction and loyalty of the customers.The concept used is about the management of strategy, the quality of service,customers loyalty, customers satisfaction and customers satisfaction strategy.Based on these cases, theory is proposed with 9 hypotheses to be tested with SEM(Stuctural Equation Modal) method. The sample of the research is 135 respondentsfrom the KJKS BMTs customers/members.The result of the analyses meets the goodness of index criteria, of which thescore chisquare is 3.5858, probability: 0.55, RMSEA: 0.55, GFI: 0.55, AGFI: 0.942,CMIN/DF: 1.214, TLI: 0.975 and CFI: 0.977. From the result of 9 hypotheses indicatean acceptable result.The result of this research indicates that there are influenceamong the service quality of reliability, guarantee, reality, empathy, response power,price, access, and closeness to the customer towards the customers satisfaction andloyalty in KJKS BMT Insan Kamil Solo.The recomendation of this research is that KJKS BMT Insan Kamil shouldimprove the quality of service( for instance, by increasing ability, hospitality of Tellerand its Customer Service and the condition of facilities and the accessibility to contactKJKS BMT Insan Kamil) refers to the questionnaire result which is widely opened toreach customers satisfaction and loyalty.The keywords: Reliability, assurance, tangibles, empathy responsiveness, price,access and customer intimacy